2015
DOI: 10.1080/00036846.2014.995360
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between South Asian stock returns and macroeconomic variables

Abstract: This article investigates whether economic variables have explanatory power for share returns in South Asian stock markets. In particular, using data for four South Asian emerging stock markets over the period 1998 -2012, the article examines the influence of a selection of local, regional and global economic variables in explaining equity returns; most previous studies that have examined this issue have tended to focus on only local and/or global factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
(24 reference statements)
0
14
0
Order By: Relevance
“…However, industrial production, interest rates, and crude oil prices are indisputably three of the most commonly used macroeconomic indicators in the empirical investigation, and these same macro variables are utilized in the present study to examine their influence on the U.S. stock prices. Researchers like Khan et al (2015) argued for the importance of considering not just domestic macroeconomic variables but also global factors especially as economies like the U.S. become more integrated internationally. Consistent with this argument, industrial production and interest rates represent the U.S. domestic macroeconomic factors while the crude oil price constitutes a global factor.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, industrial production, interest rates, and crude oil prices are indisputably three of the most commonly used macroeconomic indicators in the empirical investigation, and these same macro variables are utilized in the present study to examine their influence on the U.S. stock prices. Researchers like Khan et al (2015) argued for the importance of considering not just domestic macroeconomic variables but also global factors especially as economies like the U.S. become more integrated internationally. Consistent with this argument, industrial production and interest rates represent the U.S. domestic macroeconomic factors while the crude oil price constitutes a global factor.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A large body of empirical work (including Humpe & Macmillan, 2009; Khan, Tantisantiwong, & Fifield, 2015; Patra & Poshakwale, 2006; Ratanapakorn & Sharma, 2007; Salisu, Swaray, & Oloko, 2019) have followed the pioneer work of Fama (1981) and Chen, Roll, and Ross (1986) to examine the behaviour of the stock market and its influence by a wide variety of economic variables, such as industrial output, interest rates, crude oil prices and inflation in both advanced and less developed nations. Much of the existing body of literature which investigates this relationship has employed standard linear econometric methods.…”
Section: Introductionmentioning
confidence: 99%
“…The outcome of this study presents that growth, inflation, and employment affects the total economic policy positively and which ultimately affects the stock return in the US market. Khan, Tantisantiwong, Fifield, and Power (2015) South Asian Countries (Bangladesh, India, Sri Lanka, Pakistan) This study finds that interest rate and inflation rate have a significant effect on Pakistan. For Bangladesh, regional economic activities can explain the stock return.…”
Section: Bangladeshmentioning
confidence: 81%
“…Then, Linear ARDL Bound testing has conducted to get the evidence of having a long-run relationship among the variables and to determine, which variable can consider as the best-fitted dependent variable. After that, lag length has been selected for each of the variables and followed by it, the main ARDL test has been done to find the long-run relationship among the volatility and particular variable (Khan et al, 2015;Raza, Jawaid, Afshan, & Abd Karim, 2015). After testing the long-run effect, the short-run study has conducted.…”
Section: Discussionmentioning
confidence: 99%
“…A study, conducted in 2015 in Indian, Bangladesh, Pakistan, and Sri Lanka using VAR and Principal Components Analysis (PCA) revealed that economic factors could not explain stock returns in India. However, economic activity directly explains stock returns of Bangladesh and indirectly explains stock returns of Pakistan and Sri Lanka (Khan et al, 2015).…”
Section: Economic Variables and Stock Marketmentioning
confidence: 99%